Determinación de la capacidad alergénica de una nueva fórmula infantil a base de leche de vaca en 7 lactantes (2017)
ABSTRACT: Cow’s milk protein allergy is the main allergic problem during the first year of life, possibly owing to immune and gastrointestinal systems poor maturation. To prevent allergic reactions, the content and type of proteins in infant formulas resemble those of breast milk. We believe that reactions are due rather to the amount than to the type of protein. Objective: To design a new formula with cow’s milk that provides the infant with the main nutrients at an affordable cost and with lower risk for the development of allergies. Methods: Three-phase project: product design, industrial production and ex vivo assay to assess for anemia and type I allergic reaction by CD63 expression in basophils. Results: For every 100 calories, the content of protein was 2.0 g, carbohydrates 7.2 g and fat 0.5 g, which is higher than the indicated maximum value (4.5 g). Microbiologically, it was an innocuous food. CD63 expression was low in 57.1% of the babies and high in 42.9%. Conclusion: The new formula did not trigger any allergenic responses and can therefore be supplied to non-atopic infants.